PERFORMANCE OF WEANER RABBITS FED GRADED LEVELS OF UREA-TREATED COWPEA HUSKS DIETS - Soji, W. M.; Yusuf, H. B.; Edeh, I. E.; Yusuf, S.Z. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
A fifty six (56) days feeding trial was conducted to evaluate the performance of weaner rabbits on graded levels of urea-treated cowpea husk diets. The husks were treated at 0, 2.5, 3, 3.5 and 4% levels of urea solution designated as T1, T2, T3, T4 and T5 respectively. Forty (40) unsexed mongrel weaner rabbits aged between 5-6 weeks were used for the experiment and were randomly allotted to treatments in a Completely Randomized Design. The treatments were replicated four times with two rabbits per replicate. The rabbits were given 50g of feed twice a day (8:00am and 4:00pm) and water ad-libitum. The results from proximate composition of urea-treated cowpea husk showed improvement in protein content (11.3- 15.23%) and also fibre fraction degradation (33.1- 18.07%) from treatment 1-5 respectively. The result of growth performance revealed that there were no significant (P>0.05) differences in final body weight (1457.80- 1540.10g), total weight gain (914.13- 990.50g) and FCR (3.79-4.58) across the treatment groups. Similarly, parameters evaluated for nutrient digestibility were similar (P>0.05) across the dietary treatments. Hence t2 fed Treated cowpea husk with 2.5% urea solution gave the least cost per kg gain (₦870.74) compared to others treated with higher levels of urea and is therefore recommended for weaner rabbits.